2000
DOI: 10.1084/jem.191.3.411
|View full text |Cite
|
Sign up to set email alerts
|

The Induction of Tolerance by Dendritic Cells That Have Captured Apoptotic Cells

Abstract: What makes a protein immunogenic, particularly for strong T cell-mediated immunity? To a first approximation, this determination seems to be made by dendritic cells (DCs). Immature DCs, as in skin (1-4), lung ( 5), blood (6, 7), and spleen (7, 8), take up proteins, immune complexes, microbes, and dying cells. However, in order to use these antigens to stimulate a T cell response, the DCs must undergo a characteristic process of terminal differentiation called "maturation." The known stimuli for DC maturation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
786
1
10

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,068 publications
(820 citation statements)
references
References 59 publications
23
786
1
10
Order By: Relevance
“…Apoptotic cells are endowed with immunomodulatory properties. 16,17 Macrophages involved in apoptotic cell capture have been described to release TGF-b both in vitro 19 and in vivo. 26 A previous in vitro study reported that TGF-b was specifically released by macrophages ingesting apoptotic cells, but not during any other type of phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apoptotic cells are endowed with immunomodulatory properties. 16,17 Macrophages involved in apoptotic cell capture have been described to release TGF-b both in vitro 19 and in vivo. 26 A previous in vitro study reported that TGF-b was specifically released by macrophages ingesting apoptotic cells, but not during any other type of phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…DC subsets have also been implicated in apoptotic cell uptake 17,[20][21][22][23] and subsequent T-cell cross-tolerization. [20][21][22] In our model, we found fluorescent apoptotic bodies in splenic DC, suggesting that apoptotic cell-derived Ag can also be processed by some DC subsets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature DCs express high levels of major histocompatibility complex (MHC) class I, II and co-stimulatory molecules such as CD80 and CD86, and secrete T-helper type-1 (Th1) cytokines such as interleukin (IL)-12 and interferon (IFN)-g. DCs acquire endogenous maturation stimuli from dying cells as a danger signal when they capture cellular antigens. Lack of danger signals delays maturation of DCs and causes active suppression of DCs stimulatory capacity, leading to the induction of T-cell tolerance (Steinman et al, 2000). Shi et al (2003) have previously identified uric acid as a novel endogenous warning molecule capable of alerting the immune system within cell lysates.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the role of apoptosis in the induction or prevention of an immune response is still unclear. Indeed, some groups have demonstrated that the uptake of apoptotic cells by DC results in T cell tolerance [4][5][6]. Conversely, other groups have shown that DC that have phagocytosed apoptotic bodies from virus-infected cells can present viral antigens to cytotoxic T cells and induce a cytotoxic response [7,8].…”
Section: Introductionmentioning
confidence: 99%